1999
DOI: 10.1093/ageing/28.2.205
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of dietary aluminium intake and risk of Alzheimer's disease

Abstract: past consumption of foods containing large amounts of aluminium additives differed between people with Alzheimer's disease and controls, suggesting that dietary intake of aluminium may affect the risk of developing this disease. Larger studies are warranted to corroborate or refute these preliminary findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(56 citation statements)
references
References 24 publications
0
50
0
5
Order By: Relevance
“…In other studies, the difficulty regarding the detection of the relationship between Al concentration and AD in epidemiological studies is highlighted. It is also reported that the potential of Al existence found in some foods and in medicines, as well as in drinking water, could be a confusing factor (Rogers and Simon 1999). In 2001, Flatten performed an analysis of the studies investigating the relationship between Al levels found in the drinking water versus AD and dementia diseases seen in the local people.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the difficulty regarding the detection of the relationship between Al concentration and AD in epidemiological studies is highlighted. It is also reported that the potential of Al existence found in some foods and in medicines, as well as in drinking water, could be a confusing factor (Rogers and Simon 1999). In 2001, Flatten performed an analysis of the studies investigating the relationship between Al levels found in the drinking water versus AD and dementia diseases seen in the local people.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated in an epidemiological study that individuals who used to ingest food with high Al contents presented a two times higher risk of developing AD (14) .…”
Section: Inmentioning
confidence: 99%
“…Increased aluminium concentrations were found in the brains of deceased Alzheimer's patients. Other studies, however, have been unable to find definite indications supporting the hypothesis that aluminium plays a causative role in Alzheimer's disease or causes pathological alterations in vivo in the species studied [14][15][16][17][18][19][20].…”
Section: Introduction and Objectivementioning
confidence: 99%